Endoscopic third ventriculostomy versus ventriculoperitoneal shunt for treatment of hydrocephalus in infants in a tribal population in India - Pratik Patel; Jaiswal Gaurav; Lodha Krishna Govind; Gupta Tarun Kumar; Yadav Kaushal; Rai Abhinav Kumar (Romanian Neurosurgery, 2021)
Study design: Prospective long term follow-up study